PEMBAGIAN HARTA WARISAN BAGI ANAK LAKI-LAKI DAN PEREMPUAN BERDASARKAN HUKUM ADAT BUDAYA KARO DI DESA MANUK MULIA KECAMATAN TIGA PANAH KABUPATEN KARO - Jhon Brema Barus; Sukadi; I Nyoman Natajaya (Jurnal Media Komunikasi Pendidikan Pancasila dan Kewarganegaraan, 2022)
Customary law is an unwritten law regarding regulations that govern the life of a community and its existence will still be adhered to by people who believe in it even though these regulations are not stipulated by the authorized institution. The purposes of this study are to: To determine the process of implementing the distribution of inheritance that occurs in the family and in the Karo community. To find out what obstacles women face in the distribution of inheritance in the household and community in Karo, and to find out the position of women of the Karo tribe in the inheritance distribution system. This research is a qualitative descriptive study. Data collection techniques used are interviews, observation, and document recording. The research subjects were determined by purposive sampling technique, the research subjects were; Traditional Leaders, Head of Manuk Mulia Village, and Community Leaders. Research Results: Community inheritance system in Manuk Mulia Village, Implementation of Karo customary law in the distribution of inheritance and the position of Batak Karo women in the inheritance distribution system.